2021
DOI: 10.1177/01945998211041921
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Otolaryngology During COVID‐19: Patient and Physician Satisfaction

Abstract: Objective To examine patient and physician satisfaction with telemedicine in otolaryngology during COVID-19 and identify associated factors. Study Design Prospective cohort study. Setting Tertiary care center. Methods Patient satisfaction was rated by patients (age ≥18 years) who had encounters from May to July 2020 (n = 407). Physician satisfaction was rated by 15 otolaryngologists for specific encounters delivered from May to June 2020 (n = 1011). Patient satisfaction was measured with a Press Ganey question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
(125 reference statements)
1
20
0
Order By: Relevance
“…Nonetheless, current evidence on telemedicine implementation within otolaryngology suggests similar quality of care 9 and provider/patient satisfaction, with comparable satisfaction scores to in-person visits. 10 Telemedicine regulation has also evolved during the COVID-19 pandemic, including coverage of audio-only visits, select states eliminating patient cost sharing for telemedicine services, 11 and increased provider reimbursement for telemedicine visits. 12 Emerging evidence suggests that much work is needed to ensure that advances in telemedical care reach vulnerable populations; a recent Centers for Medicare & Medicaid Services study found that Black and rural communities utilize telemedicine the least.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, current evidence on telemedicine implementation within otolaryngology suggests similar quality of care 9 and provider/patient satisfaction, with comparable satisfaction scores to in-person visits. 10 Telemedicine regulation has also evolved during the COVID-19 pandemic, including coverage of audio-only visits, select states eliminating patient cost sharing for telemedicine services, 11 and increased provider reimbursement for telemedicine visits. 12 Emerging evidence suggests that much work is needed to ensure that advances in telemedical care reach vulnerable populations; a recent Centers for Medicare & Medicaid Services study found that Black and rural communities utilize telemedicine the least.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and providers self-reported their level of satisfaction on a visual analog scale (VAS; range 0-100) with end anchors indicating 'not at all satisfied' or 'extremely satisfied'. Patient satisfaction was additionally measured using the Telemedicine Satisfaction Questionnaire (TSQ; range 1-5), a patient-reported outcome measure that has been shown to be both reliable and valid, 32 Used in numerous studies investigating patient satisfaction with telemedicine, 15 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 the TSQ consists of 14 items scored on a 5 point Likert scale and assesses satisfaction across the quality of care provided, similarity to face-to-face encounter, and overall perception of the interaction. Patients also answered two binary questions about (1) their desire to choose telemedicine over in-person therapy in the future and (2) their internet reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Within the field of otolaryngology, patients report high levels of satisfaction with telemedicine care. 12 , 13 , 14 , 15 A recent study performed at this institution demonstrated high concordance rates in both diagnosis and management between initial telemedicine visit and subsequent laryngoscopy; 16 thus, although laryngoscopy is ultimately needed for definitive diagnosis of vocal pathologies, empiric voice therapy can be offered via telepractice in certain situations until in-person evaluation is safely performed.…”
Section: Introductionmentioning
confidence: 99%
“…The attitudes of Otolaryngology patients toward telemedicine are also favorable with a high satisfaction rate. [50][51][52][53] Perceived benefits of telehealth by patients include improved convenience and decreased costs associated with travel and parking. 52 , 54 Higher patient satisfaction has been associated with videoconference visits (vs telephone) and patients with English as a preferred language.…”
Section: Subspecialtymentioning
confidence: 99%
“…52 , 54 Higher patient satisfaction has been associated with videoconference visits (vs telephone) and patients with English as a preferred language. 53 There are barriers to telehealth to be aware of, however, which include patient access to technology, access to an interpreter, lack of trained staff, level of patient education, and patient comfort. 52 , 55 , 56 Based on an open-ended survey of Otolaryngology patients who had a video-based telehealth visit, the majority of reservations were centered around internet connection and accessing the user interface.…”
Section: Subspecialtymentioning
confidence: 99%